Patients' decisional control over care: a cross‐national comparison from both the patients' and nurses' points of view. Issue 1 (28th April 2015) - Papastavrou, Evridiki; Efstathiou, Georgios; Tsangari, Haritini; Karlou, Chryssoula; Patiraki, Elisabeth; Jarosova, Darja; Balogh, Zoltan; Merkouris, Anastasios; Suhonen, Riitta
Abstract : Background: Patients' decisional control over care is the ability or power for patients to decide what their involvement will be in healthcare decisions. There is evidence of limited agreement between the perceptions of patients and the perceptions of nurses and/or caregivers with regard to the degree of patient involvement in the planning and performance of their care. Aim: To analyse and compare patients' and nurses' perceptions of patients' decisional control over their own care. Method: A multisite cross‐sectional comparative survey design was employed. Data were collected from hospitalised surgical inpatients (n = 1315) and their caregivers (n = 960 nurses) in five European countries. The Individualised Care Scale part B was used for collecting data from both the patients and nurses. Ethical standards were followed throughout the study. Results: Significant between‐country differences were found between patients and nurses. In all countries, both patients and nurses regarded that decisional control over care had been actualised (ICS‐B: M = 3.75–4.47 and 3.48–4.33, respectively), but there were significant differences in their perceptions regarding four of the six items of the decisional control factor of the ICS‐B. Conclusions: The results show that there are disparities between patients' and nurses' perceptions of patient involvement in care, probably due to cultural issues that need further exploration. Clinical relevance: The disparities between patients' and nurses' perceptions on patients' decisional control over their care should be taken into consideration as a potential cause of patient dissatisfaction with nursing care.